Antibacterial Property of Composites of Reduced Graphene Oxide with Nano-Silver and Zinc Oxide Nanoparticles Synthesized Using a Microwave-Assisted Approach - Hsueh, Yi-Huang (Int J Mol Sci, 2019)
Graphene oxide (GO) composites with various metal nanoparticles (NPs) are attracting increasing interest owing to their broad scope in biomedical applications. Here, microwave-assisted chemical reduction was used to deposit nano-silver and zinc oxide NPs (Ag and ZnO NPs) on the surface of reduced GO (rGO) at the following weight percentages: 5.34% Ag/rGO, 7.49% Ag/rGO, 6.85% ZnO/rGO, 16.45% ZnO/rGO, 3.47/34.91% Ag/ZnO/rGO, and 7.08/15.28% Ag/ZnO/rGO. These materials were tested for antibacterial activity, and 3.47/34.91% Ag/ZnO/rGO and 7.08/15.28% Ag/ZnO/rGO exhibited better antibacterial activity than the other tested materials against the gram-negative bacterium Escherichia coli K12. At 1000 ppm, both these Ag/ZnO/rGO composites had better killing properties against both E. coli K12 and the gram-positive bacterium Staphylococcus aureus SA113 than Ag/rGO and ZnO/rGO did. RedoxSensor flow cytometry showed that 3.47/34.91% Ag/ZnO/rGO and 7.08/15.28% Ag/ZnO/rGO decreased reductase activity and affected membrane integrity in the bacteria. At 100 ppm, these two composites affected membrane integrity more in E. coli, while 7.08/15.28% Ag/ZnO/rGO considerably decreased reductase activity in S. aureus. Thus, the 3.47/34.91% and 7.08%/15.28% Ag/ZnO/rGO nanocomposites can be applied not only as antibacterial agents but also in a variety of biomedical materials such as sensors, photothermal therapy, drug delivery, and catalysis, in the future.